2016
DOI: 10.31768/2312-8852.2016.38(3):158-168
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism of natural terpenoids as NF-kB inhibitors: an overview on their anticancer potential

Abstract: The transcription factor, nuclear factor kappa B (NF-kB) is one of the principal inducible protein in mammals known to control the gene expression in many critical physiological responses such as oxidative stress, inflammation etc. and has been shown to play an important role in the pathogenesis of cancer. Terpenoids are major constituents present in nutritionally used fruits, vegetables and different spices which possess various pharmacological action including anticancer activity. Various terpenoids, viz. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
0
22
0
1
Order By: Relevance
“…It was reported that several key genes in the inflammatory process such as NF- κ B provide a mechanistic link between inflammation and cancer [4548]. Activation of TLRs and TNFR leads to NF- κ B activation and induced the expression of many proinflammatory molecules including NO synthase 2 (iNOS) [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that several key genes in the inflammatory process such as NF- κ B provide a mechanistic link between inflammation and cancer [4548]. Activation of TLRs and TNFR leads to NF- κ B activation and induced the expression of many proinflammatory molecules including NO synthase 2 (iNOS) [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB activity is mediated by numerous signaling pathways such as mitogen-activated protein kinases (MAPKs) and IκB kinase (IKK). The upregulation of IKK complexes phosphorylate the IκB subunits of NF-κB/IκB and subsequently activate the NF-κB (Jain et al, 2016 ). IKK activity is triggered during aging by NF-κB (Kim et al, 2002 ), which further modulates the p38 MAPK, extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinases (JNKs) pathways that modulate the NF-κB-dependent transcriptional activity during the inflammatory reaction.…”
Section: Molecular Inflammation Involved During Agingmentioning
confidence: 99%
“…A plethora of compounds consisting of small molecules, biologics, inhibitory peptides, and many other different types of bioactive molecules have been identified as inhibitors of NF-κB and categorized into different groups based on the stage of NF-κB activation at which they exert their inhibitory effects [ 111 , 112 , 113 , 114 ]. These groups include agents that act at various steps of NF-κB signaling at (i) upstream of IKK, (ii) directly affecting the IKK complex or IκB phosphorylation, (iii) ubiquitination or proteasomal degradation of IκB, (iv) nuclear translocation of NF-κB, (v) NF-κB DNA binding, and (vi) NF-κB-directed gene transactivation.…”
Section: Inhibitors Of Nf-κb Function and Selected Pharmacologicalmentioning
confidence: 99%